2013
DOI: 10.1007/s40436-013-0046-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of defect density on the ZnO nanostructures of dye-sensitized solar cells

Abstract: The relationship between bilayer nanostructure, defect density and dye-sensitized solar cell (DSCC) performances was investigated. By adjusting bilayer nanostructures, defect density of ZnO nanodendrite-nanorods structure was decreased comparing to that of nanoflowernanorods structure. The performances of DSCC based on ZnO nanodendrites-nanorods structure and nanoflowernanorods structure were studied by Raman spectrum, room temperature photoluminescence, dye loading, photocurrent density-voltage characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Although the synthesis and DSSC performance of various solution-derived ZnO rods have been reported in a series of reviews and articles, the efficiencies of most of them were below 1% with a few exhibiting above 1% efficiency. In this respect, our data are far superior in that we were able to prepare ZnO rods by a very simple solution technique without the use of any surfactant or structure-directing agent exhibiting much enhanced DSSC efficiency as compared to many of the reported values on solution processed ZnO rods. , …”
Section: Results and Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Although the synthesis and DSSC performance of various solution-derived ZnO rods have been reported in a series of reviews and articles, the efficiencies of most of them were below 1% with a few exhibiting above 1% efficiency. In this respect, our data are far superior in that we were able to prepare ZnO rods by a very simple solution technique without the use of any surfactant or structure-directing agent exhibiting much enhanced DSSC efficiency as compared to many of the reported values on solution processed ZnO rods. , …”
Section: Results and Discussionmentioning
confidence: 72%
“…This sample exhibited a higher open circuit voltage ( V oc ) of 0.71 V and a lower fill factor (FF) of 35.2. The lower free carrier density in the 300 °C annealed sample could induce a positive shift of the Fermi level of ZnO rods that could further reduce the gap between the I – /I 3– redox couple and Fermi level, thereby minimizing the V oc followed by an improvement in fill factor, which is less recombination and thereby enhances the efficiency indirectly. ,,, The as-prepared and 300 °C annealed ZnO rods having less oxygen vacancy density exhibited relatively less V oc of 0.66 and 0.67 V, respectively (Figure a) and a higher fill factor of 43.58% and 45.29%, respectively (Figure c). The photoluminescence and Raman spectroscopic studies confirmed that the 300 °C annealed rods have minimum defects with improved crystal quality.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of studies conducted on point defects have focused on either identifying or computationally predicting their stability. , Other works describe changes in defect density qualitatively through the increase or decrease of a spectroscopic band signal . For quantifying defect density, techniques such as deep level transient spectroscopy (DLTS) and impedance spectroscopy are the most commonly used but both require contacts for an external electrical connection and DLTS is also only sensitive to deep level defects. , Techniques that do not require contacts are usually either spectroscopy or microscopy based such as lyoluminescence and Raman spectroscopy. , These methods are, however, often restricted to bulk sample measurements.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this aim, metal oxide semiconductors are utilized as a photoanode in the photoelectrochemical cells. Among oxide-based semiconductors, ZnO is the most encouraging candidate due to its high earth plenty, nontoxicity, and unique physical and chemical properties for many photovoltaic applications [1]. Owing to the large band gap energy of ZnO (3.37 eV), the electron-hole (e --h + ) pairs are formed when it is irradiated by ultraviolet (UV) light which represents merely (4%) of the entire solar light spectrum.…”
Section: Introductionmentioning
confidence: 99%